(untitled) (Medical Forum Monthly, 2024)
ABSTRACT Objective: To compare the liver enzymes between hypertensive and normal subjects. Study Design: Cross-sectional, descriptive study. Place and Duration of Study: Basic Medical Sciences Institute, J.P.M.C, Nehal Hospital and Shamsi Hospital Karachi, from December 2006 to March 2011. Materials and Methods: The study has compared the liver enzymes and associated cardiovascular risk factors like blood pressure, BMI, waist hip ratio, blood sugar, lipid profile between 100 normal and 100 hypertensive subjects. The assessment was done by applying independent t test and Pearson correlation using statistical package for social sciences 15. Results: The normal and hypertensive subjects were compared with liver enzymes, systolic and diastolic blood pressure, lipid profile, BMI and waist/hip ratio. All values showed significant correlation (P < 0.001) using independent t test. In the hypertensive subjects all the liver enzymes were found to be raised in comparison with hypertensive but were within their normal ranges. The levels of GGT (Gamma glutamyl transferase) was found to be raised beyond its normal range and was compared according to type I and Type II stage of hypertension and was found to be raised significantly. Conclusion: Among all the liver enzymes compared with uncontrolled hypertensive GGT was found to be most significantly correlated with all the factors increasing cardiovascular risk, and needs to be measured in every hypertensive individual.